# How do you solve for x in #C=b-bx#?

##### 2 Answers

Apr 27, 2018

#### Answer:

#### Explanation:

Let's start by rewriting as

#bx - b = -C#

Now factor

#b(x- 1) = -C#

#x - 1 = -C/b#

#x = 1 - C/b#

Hopefully this helps!

Apr 27, 2018

#### Answer:

#### Explanation:

You can separate the constants from the variable with algebraic operations. In this case we will still end up with an expression in C and b, as they are not given values.

NOW, given any C and b, x can be calculated directly.